Diversity and assessment of trees on one-hectare plot in Mt. Musuan, Bukidnon basis for long term monitoring and conservation - Amoroso, Victor B.; Villar, Ricardo G.; Aribal, Lowell G. (2014)
The study was conducted to determine the diversity and status of trees in one-hectare plot of Mt. Musuan, Bukidnon. Six sampling plots, measuring 20 x 20 m area within 1 - ha plot, were established to compute the diversity index and generate tree profile. The specimens collected were classified and identified using the taxonomic keys, journals, and monographs. Assessment of trees was determined based on the International Union for Conservation of Nature (IUCN) and the list of Philippine threatened plants. Inventory of trees in one-hectare plot revealed 77 species which were placed in 65 genera, 36 families, and with a total of 419 individuals. Sampling plots with a total area of 2400 m2 showed 30 species, 28 genera, and 22 families. Senna spectabilis (DC.) H.S. Irwin & Barneby represents 15% (63 individuals) of the total number of individuals. Furthermore, the mean of 8.1 species/20 x20 m plot was recorded. Species' diversity of trees in different locations showed that it had a mean diversity value of H = 0.77. In four sampling plots, S. spectabilis showed the highest species importance value (SIV) while in two other plots Kleinhovia hospital L. and Oroxylum indicum (L.) Kurz obtained the highest SIV. Assessment of conservation status of trees showed one critically endangered species (Pterocarpus indicus Willdenow), three vulnerable species, four endemic species, 17 depleted species, five common species, four rare species, and 32 economically important species.
Keywords: Mt. Musuan (Bukidnon); Forest conservation; Forest ecology; Forest management; Mindanao studies; Tree inventory